Answered step by step
Verified Expert Solution
Question
1 Approved Answer
Haskell assignment (without imports) 1) Given the following defenitions (m1) map f [] = [] (m2) map f (x:xs) = f x : map f
Haskell assignment (without imports)
1)
Given the following defenitions
(m1) map f [] = []
(m2) map f (x:xs) = f x : map f xs
(c1) [] ++ ys = ys
(c2) (x:xs) ++ ys = x : (xs ++ ys)
prove that for all lists xs and ys:
map f (xs ++ ys) = (map f xs) ++ (map f ys)
Step by Step Solution
There are 3 Steps involved in it
Step: 1
Get Instant Access to Expert-Tailored Solutions
See step-by-step solutions with expert insights and AI powered tools for academic success
Step: 2
Step: 3
Ace Your Homework with AI
Get the answers you need in no time with our AI-driven, step-by-step assistance
Get Started